Pengembangan Pariwisata Halal di Semarang dengan Mengoptimalkan Kearifan Lokal melalui Konsep Smart Tourism - Rahman, Alfina Aulia; Kusumastuti, Anita; Ulla R.J, Winda Aulia; Listiani, Wulan (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2021)
Indonesia is a country with the 2nd most halal tourist place in the world. Many provinces and tourist destinations in Indonesia have implemented halal tourism programs by carrying out the concept of local wisdom and trying to attract many tourists to visit. Halal Tourism itself is a cultural-based tourism that applies Islamic values as its foundation. One city that has begun to develop halal tourism is the city of Semarang. The purpose of this study is to see the development of halal tourism in the city of Semarang by optimizing local wisdom through the concept of smart tourism. The approach used in this study is a qualitative and using systematic literature review as a method. The results of this study indicate that the tourism sector has a positive contribution to the economy because it can increase the number of visitors and investment. Therefore, this sector can become one of the main factors in increasing country's foreign exchange earnings, increasing employment, as well as business and infrastructure development. To develop more halal tourism sector, it is certainly to develop access of information and transportation.